Humor and Catachresis in Emily Dickinson’s Death Poetry - Tóth, Zsófia Anna (AMERICANA E-journal of American Studies in Hungary, 2019)
The paper discusses how Emily Dickinson, with the help of humor and catachresis – both of which work with the logic of defamiliarization/refamiliarization –, tries to reinterpret death as an experience, as a state of being or as an E/entity that we all encounter inevitably. The paper argues that Dickinson refused to be intimidated by the traditional concepts of death/Death and she consciously approached it/It with humor as well as through catachresis to shake our notions and force us to see the whole issue from a new perspective. For Dickinson, death was never a final destination, it was always a door and a new avenue for greater knowledge, wisdom and exciting adventures. The paper analyzes some of her most unorthodox (and well-known) poems about death and dying to support these claims after overviewing the scholarly research on her death poetry (that traditionally also treated it as tragic and there were only occasional instances when her humor was pointed out) as well as some theoretical arguments about the workings of humor, catachresis and some reflections on the relationship between women and humor.